Kajian Tartibunnuzul Dan Sababunnuzul Dalam Ayat-Ayat Khamr Bagi Pengembangan Metode Dakwah - Sudury, Ahmad Miftahus; Al Faruq, Abdul Qudus; Thobroni, Ahmad Yusam (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
The phenomenon of alcohol addiction in Indonesia has rapidly spread across various demographics, from the elderly to the youth. A strategic approach to addressing this issue involves drawing upon the gradual prohibition of alcohol (khamr) established during the Prophet Muhammad’s time. This study aims to examine the stages and processes of khamr prohibition in early Islam as a reflection for contemporary challenges. The research adopts a qualitative methodology, sourcing information from books and other literature (Library Research), and applies a descriptive historical analysis to integrate Tartibunnuzul (chronological order of revelation) and Sababunnuzul (context of revelation) approaches. Findings reveal that the Prophet’s method addressed alcohol prohibition progressively, starting with prohibiting intoxication during prayer (An-Nisa [4]: 43), encouraging contemplation on its benefits and harms (Al-Baqarah [2]: 219), and finally, establishing an absolute prohibition (Al-Maidah [5]: 219). This gradual approach proved psychologically effective and presents valuable insights for addressing modern-day challenges in dakwah.